Method for manufacturing wafer based on chemical etching method
By using chemical corrosion method and acid corrosion mixture during the wafer manufacturing process, combined with laser modification treatment, the risk of fragmentation caused by ultrasonic vibration and high roughness of the separation surface are solved, and more efficient and uniform wafer separation and surface treatment are achieved.
Patent Information
- Application Number
- CN202411619633.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-28
AI Technical Summary
The existing ultrasonic vibration methods have problems with fragmentation risks and high separation surface roughness during the wafer separation process, resulting in long processing time of subsequent grinding processes and large grinding wheel losses.
The method based on chemical corrosion method is adopted to modify the ingot to be cut through a laser, and the modified layer is corroded with an acid corrosion mixture added with polyoxyethylene ether-based surfactant to separate the wafer.
This method avoids the risk of debris caused by ultrasonic vibration, and the separation process is gentler. It can evenly remove the laser ablation layer, reduce the roughness of the separation surface, improve surface flattening, and reduce the processing time and grinding wheel loss in subsequent grinding processes.
Smart Images

Figure CN119530988A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of chip technology, and in particular to the field of wafer manufacturing technology. Background Art
[0002] The existing method of manufacturing wafers by laser modification, such as the technical solution disclosed in the patent publication number CN116890174A, mainly includes two processes: 1. The stripping starting point forming process, the focusing point of the laser light with a wavelength that is transparent to the ingot is positioned at a depth corresponding to the thickness of the wafer to be manufactured from the end face of the ingot, and the laser light is irradiated to the ingot to form a modified layer and a stripping starting point; 2. The stripping process, the wafer to be manufactured is stripped from the ingot from the stripping starting point, in which degassed water is provided to the end face of the ingot to generate a degassed water layer and ultrasonic waves are applied to destroy the stripping starting point. That is, in the existing technical solution, the modified ingot is vibrated by ultrasonic vibration in the stripping process, so that the wafer is separated from the ingot to obtain the manufactured wafer.
[0003] However, the existing ultrasonic vibration method has the risk of fragmentation and the separated wafers are rough, resulting in long processing time and excessive wear of the grinding wheel in the subsequent grinding process. Summary of the invention
[0004] The present disclosure provides a method for manufacturing a wafer based on a chemical etching method, which is used to avoid the risk of fragmentation caused by ultrasonic vibration and improve the ablation efficiency and uniformity of a laser ablation layer.
[0005] In a first aspect of the present disclosure, a method for manufacturing a wafer based on a chemical etching method is provided, the method comprising:
[0006] Performing a modification process on the ingot to be cut by a laser to form at least one modified layer;
[0007] Based on an acidic etching mixed solution to which a polyoxyethylene ether surfactant is added, an etching treatment is performed on a crystal ingot to be cut which forms at least one modified layer, thereby obtaining at least one wafer.
[0008] Optionally, the polyoxyethylene ether surfactant is one or a mixture of Triton X-100, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and isomeric alcohol polyoxyethylene ether.
[0009] Optionally, the polyoxyethylene ether surfactant is Triton X-100, and the volume fraction of Triton X-100 is 0.5% to 1.5%.
[0010] Optionally, the volume fraction of Triton X-100 is 1%.
[0011] Optionally, the acidic corrosion mixture also includes hydrofluoric acid and nitric acid, wherein the ratio of hydrofluoric acid to nitric acid is 3:1.
[0012] Optionally, the method further comprises:
[0013] The acidic corrosive mixed solution is subjected to ultrasonic vibration treatment, and the vibration frequency is 1.8 to 2.2 times the inherent vibration frequency of the material.
[0014] Optionally, the vibration frequency is twice the natural vibration frequency of the material.
[0015] Optionally, the laser is a multi-mode continuous green laser with a laser light wavelength of 532 nm.
[0016] Optionally, the ingot to be cut is subjected to a modification process by a laser to form at least one modified layer, comprising:
[0017] a modification step, controlling the focal point of the laser light of the multi-mode continuous green laser to be located at a predetermined depth from the end face of the ingot to be cut, and performing interpolation motion to form a spiral burning point, thereby forming a modified layer at a predetermined depth from the end face of the ingot to be cut; the predetermined depth is determined based on the number and thickness of the wafers to be manufactured;
[0018] a depth-changing and re-modifying step, wherein after the previous modification step is completed, the focal point of the laser light of the multi-mode continuous green laser is changed to be located at a depth from the end face of the crystal ingot to be cut, and the focal point of the laser light of the multi-mode continuous green laser is controlled to be located at a changed depth from the end face of the crystal ingot to be cut, and an interpolation movement is performed to form a spiral burning point, and a modified layer at a predetermined depth from the end face of the crystal ingot to be cut is formed; the changed depth is determined based on the number and thickness of the corresponding wafers to be manufactured;
[0019] The aforementioned step of changing the depth and then modifying is repeated until a predetermined number of modified layers are obtained for the crystal ingot to be cut.
[0020] Optionally, the crystal ingot to be cut is a silicon carbide ingot.
[0021] The present disclosure provides a method for manufacturing a wafer based on a chemical etching method, comprising: modifying a crystal ingot to be cut by a laser to form at least one modified layer; etching the crystal ingot to be cut with at least one modified layer based on an acidic etching mixed solution to which a polyoxyethylene ether surfactant is added, to obtain at least one wafer. That is, the wafer is separated from the crystal ingot by etching with an acidic etching mixed solution, and the separation process is gentler, which can avoid the risk of fragments caused by ultrasonic vibration, and can also evenly remove the laser burning point, while reducing the roughness of the separation surface, improving the surface flatness, and reducing the processing time and the loss of the grinding wheel in the subsequent grinding process. In addition, during the etching process of the acidic etching mixed solution on the laser modified layer, part of hydrogen will be generated while the modified layer is dissolved, thereby forming a mixed solution flow channel in the modified layer. The present disclosure can enhance the wettability of the mixed solution and promote the flow of the mixed solution by adding a polyoxyethylene ether surfactant, and can prevent the growth of bubbles to hinder the contact between the removed object and the mixed solution, thereby improving the ablation efficiency and uniformity of the laser ablation layer.
[0022] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to better understand the present solution and do not constitute a limitation of the present disclosure.
[0024] Figure 1 It is a schematic flow chart of a method for manufacturing a wafer based on a chemical etching method provided by an embodiment of the present disclosure;
[0025] Figure 2 is a schematic diagram of the energy distribution of a single-mode laser;
[0026] Figure 3 is a schematic diagram of the energy distribution of multi-mode lasers;
[0027] Figure 4 It is a schematic diagram of the damage layer caused by single-mode laser and multi-mode laser;
[0028] Figure 5 It is a schematic diagram of the helical burning point formed by the interpolation motion of the laser;
[0029] Figure 6 This is an example diagram of the etching liquid flow path of the laser modified layer. DETAILED DESCRIPTION
[0030] The following is a description of exemplary embodiments of the present disclosure in conjunction with the accompanying drawings, including various details of the embodiments of the present disclosure to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present disclosure. Similarly, for the sake of clarity and conciseness, descriptions of well-known functions and structures are omitted in the following description.
[0031] Embodiment 1
[0032] Figure 1 A method for manufacturing a wafer based on a chemical etching method provided by an embodiment of the present disclosure is shown, and the method includes:
[0033] Step S101, modifying the ingot to be cut by laser to form at least one modified layer;
[0034] The crystal ingot to be cut may be a silicon carbide crystal ingot, a gallium nitride crystal ingot, or other crystal ingots to which the method disclosed herein is applicable.
[0035] Specifically, a laser with a wavelength that is transparent to the crystal ingot to be cut can be selected to perform a modification process on the crystal ingot to be cut, so as to obtain at least one modified layer.
[0036] Specifically, a multi-mode continuous green laser with a wavelength of 532nm can be used to modify the ingot to be cut to obtain at least one modified layer. The 532nm laser has both good transparency to the material and a smaller focused spot, which causes less damage to the material. For example, according to Spot size = 4M 2 *Wavelength*f / ΠD shows that the focused spot of 532nm is smaller than that of 1064nm. At the same time, because the focused spot is smaller, the thermal impact caused is also smaller than that of 1064. The focused spot of 1064nm laser is large, and the thermal impact is large, which causes more damage to the material. More material damage will increase the cost on the one hand, and the cost of subsequent grinding process consumables on the other hand, and the subsequent grinding processing time will also be longer. In addition, the laser is a device that uses the principle of stimulated radiation to amplify or oscillate light in certain excited substances. The essential difference between a single-mode laser and a multi-mode laser is that there is only one mode in the output beam mode of a single-mode laser, while there are multiple modes in the output beam mode of a multi-mode laser. The difference in mode will directly affect the spatial distribution of energy. From the perspective of energy distribution, a single-mode laser presents a typical Gaussian distribution, such as Figure 2 As shown in the figure, the three-dimensional graph is a sharp peak, while the multi-mode laser presents a typical flat-top distribution, such as Figure 3As shown in the figure, the three-dimensional image of an inverted cup has relatively even energy, which can make the processing effect more uniform, reduce the roughness of the separation surface, improve the surface flatness, and reduce the processing time and grinding wheel loss of the subsequent grinding process. Figure 4 As shown in the figure, it is a schematic diagram of the damage layer caused by single-mode laser and multi-mode laser. The damage caused by single-mode is more in the direction perpendicular to the material surface, while that caused by multi-mode is less. Therefore, the damage to the material by using multi-mode laser is relatively reduced, which can reduce material loss and thus reduce costs.
[0037] Among them, the modification treatment can be: controlling the focal point of the laser light of the green laser to be located at a first depth from the end face of the ingot to be cut, and performing interpolation movement to form a spiral burning point, forming a first modified layer at a first depth from the end face of the ingot to be cut; wherein the first depth is determined based on the thickness of a wafer to be manufactured.
[0038] The ingot to be cut can be modified, and chemical etching can be performed after obtaining a modified layer. Chemical etching can also be performed after obtaining multiple modified layers. The scheme of obtaining multiple modified layers and then performing etching can be:
[0039] a modification step, controlling the focal point of the laser light of the multi-mode continuous green laser to be located at a predetermined depth from the end face of the ingot to be cut, and performing interpolation motion to form a spiral burning point, thereby forming a modified layer at a predetermined depth from the end face of the ingot to be cut; the predetermined depth is determined based on the number and thickness of the wafers to be manufactured;
[0040] a depth-changing and re-modifying step, wherein after the previous modification step is completed, the focal point of the laser light of the multi-mode continuous green laser is changed to be located at a depth from the end face of the crystal ingot to be cut, and the focal point of the laser light of the multi-mode continuous green laser is controlled to be located at a changed depth from the end face of the crystal ingot to be cut, and an interpolation movement is performed to form a spiral burning point, and a modified layer at a predetermined depth from the end face of the crystal ingot to be cut is formed; the changed depth is determined based on the number and thickness of the corresponding wafers to be manufactured;
[0041] The aforementioned step of changing the depth and then modifying is repeated until a predetermined number of modified layers are obtained for the crystal ingot to be cut.
[0042] In the field of CNC machine tools, the contour of a part is often diverse, including straight lines, arcs, and arbitrary curves. The cutting tool of a CNC machine tool often cannot move along the actual contour of the curve, but moves approximately along several very small straight lines, and the direction of the movement is generally in the x and y directions. The interpolation methods include: linear interpolation, circular interpolation, parabola interpolation, spline interpolation, etc. Specifically, the interpolation motion described in the present disclosure is the process in which the laser control system determines the laser motion trajectory of the laser according to a certain method.
[0043] Among them, the present invention discloses a method for interpolating motion to form a spiral burning point, such as Figure 5 As shown, the laser is focused inside the material, forming laser ablation points inside the material, and the ablation points are distributed inside the ingot / wafer at a specific spacing. In addition, the laser only needs to scan the object to be processed once to avoid repeated scanning, which causes laser damage superposition and increases material loss. Among them, the thickness of the silicon carbide wafer can be set according to specific needs, such as 500 microns, then the focal point is located at a predetermined depth of about 500 microns from the end face of the ingot to be cut. If it is two modified layers, under the same wafer thickness (500 microns), the corresponding changed depth of the second modified layer is about greater than 1000 microns. If the required wafer thickness is different, such as the first piece is 500 microns and the second piece is 600 microns, the corresponding focal point is located at a predetermined depth of 500 microns from the end face of the ingot to be cut, and the corresponding changed depth of the second modified layer is about greater than 1100 microns. Specifically, the distance between adjacent spiral lines is 0.08-0.12 mm. Preferably, the distance between adjacent spiral lines is 0.1 mm. Combined with the focused spot size and multi-mode laser: The 0.1mm spot effect is determined by the size of the focused spot. The size of the focused spot on the two-dimensional plane in the XY direction is about 0.1mm. Setting a spacing of 0.1mm can reduce the overlap rate of the spot and speed up the scanning speed. The single-mode spot is generally around 0.02mm after focusing.
[0044] Step S102, based on the acidic etching mixed solution added with polyoxyethylene ether surfactant, the ingot to be cut with at least one modified layer is subjected to etching treatment to obtain at least one wafer.
[0045] Specifically, an acidic etching mixture including a polyoxyethylene ether surfactant, hydrofluoric acid (HF), and nitric acid (HNO3) can be used to etch the ingot to be cut that forms at least one modified layer to obtain at least one wafer.
[0046] The polyoxyethylene ether surfactant is a mixture of one or more of Triton X-100, OP-10 alkylphenol polyoxyethylene ether, AEO-5 fatty alcohol polyoxyethylene ether, and XP-90 isomeric alcohol polyoxyethylene ether.
[0047] The present disclosure provides a method for manufacturing a wafer based on a chemical etching method, comprising: modifying a crystal ingot to be cut by a laser to form at least one modified layer; etching the crystal ingot to be cut with at least one modified layer based on an acidic etching mixed solution to which a polyoxyethylene ether surfactant is added, to obtain at least one wafer. That is, the wafer is separated from the crystal ingot by etching with an acidic etching mixed solution, and the separation process is gentler, which can avoid the risk of fragments caused by ultrasonic vibration, and can also evenly remove the laser burning point, while reducing the roughness of the separation surface, improving the surface flatness, and reducing the processing time and the loss of the grinding wheel in the subsequent grinding process. In addition, during the etching process of the acidic etching mixed solution on the laser modified layer, part of hydrogen will be generated while the modified layer is dissolved, thereby forming a mixed solution flow channel in the modified layer. The present disclosure can enhance the wettability of the mixed solution and promote the flow of the mixed solution by adding a polyoxyethylene ether surfactant, and can prevent the growth of bubbles to hinder the contact between the removed object and the mixed solution, thereby improving the ablation efficiency and uniformity of the laser ablation layer.
[0048] The present disclosure provides a possible implementation method, wherein the ingot to be cut is a silicon carbide ingot, and the silicon carbide ingot to be cut is modified by a multi-mode green laser with a laser light wavelength of 532nm and then placed in an acidic etching mixture. The acidic etching mixture also includes a ratio of hydrofluoric acid to nitric acid of 3:1, and the polyoxyethylene ether surfactant is Triton X-100.
[0049] like Figure 5 As shown in the figure, after the laser is used to modify the silicon carbide ingot, the peeling layer (laser ablation layer) is separated from SiC into Si particles and modified parts of C particles. During the etching process of the acidic etching mixed liquid on the Si / C and the composite in the laser modified layer, Si is dissolved and part of hydrogen is generated, thereby forming a mixed liquid (i.e. Figure 6 By adding polyoxyethylene ether surfactants, the wettability of the mixed liquid can be enhanced, the flow of the mixed liquid can be promoted, and at the same time, bubbles can be prevented from growing and hindering the contact between the removed object and the mixed liquid.
[0050] In the embodiment of the present disclosure, the wafer is separated from the ingot by etching with an acidic etching mixed liquid, thereby avoiding the risk of fragments caused by ultrasonic vibration. In addition, during the etching of Si / C and the composite in the laser modified layer by the acidic etching mixed liquid, part of hydrogen will be generated while Si is dissolved, thereby forming a mixed liquid flow channel in the modified layer. The present disclosure can enhance the wettability of the mixed liquid and promote the flow of the mixed liquid by adding a polyoxyethylene ether surfactant, and at the same time prevent the growth of bubbles that hinder the contact between the removed object and the mixed liquid, thereby improving the ablation efficiency and uniformity of the laser ablation layer.
[0051] The present disclosure provides a possible implementation method, wherein the ingot to be cut is a silicon carbide ingot, and the silicon carbide ingot to be cut is modified by a multi-mode green laser with a laser light wavelength of 532nm and then placed in an acidic etching mixture. The acidic etching mixture also includes a ratio of hydrofluoric acid to nitric acid of 3:1, and the polyoxyethylene ether surfactant is Triton X-100. The volume fraction of Triton X-100 is 1%.
[0052] The inventors of the present application changed the volume fraction of Triton X-100 and measured the corrosion time required for different volume fractions, as shown in the following table.
[0053] Volume fraction of Triton X-100 Corrosion time 0 5 minutes 0.1% 3.5 minutes 0.2% 2 minutes 0.5% 50 seconds 1% 45 seconds 1.5% 51 seconds 2% 55 seconds 5% 2 minutes
[0054] By referring to the experimental results in the above table, it can be understood that the volume fraction of Triton X-100 is better at 0.5% to 1.5%, and 1% is the best, and the corrosion time is the shortest.
[0055] In the embodiment of the present disclosure, the volume fraction of Triton X-100 is 1%, which can reduce the required corrosion time.
[0056] The present disclosure provides a possible implementation method, wherein the ingot to be cut is a silicon carbide ingot, the acidic etching mixture also includes a ratio of hydrofluoric acid to nitric acid of 3:1, the polyoxyethylene ether surfactant is Triton X-100, and the volume fraction of Triton X-100 is 1%. The acidic etching mixture is subjected to ultrasonic vibration treatment. The vibration frequency is 1.8 to 2.2 times the inherent vibration frequency of the material. Specifically, the vibration frequency is twice the inherent vibration frequency of the material. In addition, the acidic etching mixture can also be subjected to heat treatment. Specifically, a bow-shaped heating rod can be added to the acidic etching solution to make the heating more uniform and rapid.
[0057] In the disclosed embodiment, the acidic etching mixture is vibrated by ultrasonic waves, which can accelerate the penetration and corrosion rate of the acidic solution. In addition, the vibration frequency is not the same as the inherent vibration frequency of the crystal ingot, which will not cause fragments.
[0058] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.
[0059] The above specific implementations do not constitute a limitation on the protection scope of the present disclosure. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modification, equivalent substitution and improvement made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A method for manufacturing a wafer based on a chemical etching method, characterized in that: include: Performing a modification process on the ingot to be cut by a laser to form at least one modified layer; Based on an acidic etching mixed solution to which a polyoxyethylene ether surfactant is added, an etching treatment is performed on a crystal ingot to be cut which forms at least one modified layer, thereby obtaining at least one wafer.
2. The method according to claim 1, characterized in that: The polyoxyethylene ether surfactant is one or a mixture of Triton X-100, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and isomeric alcohol polyoxyethylene ether.
3. The method according to claim 2, characterized in that: The polyoxyethylene ether surfactant is Triton X-100, and the volume fraction of Triton X-100 is 0.5% to 1.5%.
4. The method according to claim 3, characterized in that: The volume fraction of the Triton X-100 is 1%.
5. The method according to claim 1, characterized in that: The acidic corrosion mixture also includes hydrofluoric acid and nitric acid, wherein the ratio of hydrofluoric acid to nitric acid is 3:
1.
6. The method according to claim 2, characterized in that: The method further includes: The acidic corrosive mixed solution is subjected to ultrasonic vibration treatment, and the vibration frequency is 1.8 to 2.2 times the inherent vibration frequency of the material.
7. The method according to claim 6, characterized in that: The vibration frequency is twice the natural vibration frequency of the material.
8. The method according to any one of claims 1 to 7, characterized in that: The laser is a multi-mode continuous green laser with a laser light wavelength of 532nm.
9. The method according to claim 8, characterized in that: The method comprises: performing a modification process on the ingot to be cut by a laser to form at least one modified layer, comprising: a modification step, controlling the focal point of the laser light of the multi-mode continuous green laser to be located at a predetermined depth from the end face of the ingot to be cut, and performing interpolation motion to form a spiral burning point, thereby forming a modified layer at a predetermined depth from the end face of the ingot to be cut; the predetermined depth is determined based on the number and thickness of the wafers to be manufactured; a depth-changing and re-modifying step, wherein after the previous modification step is completed, the focal point of the laser light of the multi-mode continuous green laser is changed to be located at a depth from the end face of the crystal ingot to be cut, and the focal point of the laser light of the multi-mode continuous green laser is controlled to be located at a changed depth from the end face of the crystal ingot to be cut, and an interpolation movement is performed to form a spiral burning point, and a modified layer at a predetermined depth from the end face of the crystal ingot to be cut is formed; the changed depth is determined based on the number and thickness of the corresponding wafers to be manufactured; The aforementioned step of changing the depth and then modifying is repeated until a predetermined number of modified layers are obtained for the crystal ingot to be cut.
10. The method according to claim 8, characterized in that The crystal ingot to be cut is a silicon carbide ingot.
Citation Information
Patent Citations
Wafer manufacturing method
CN116890174A